Importance of Remote Sensing Data in The Study of Land Resources - SH.Y.Sattorov; A.M.Abdulloyev; A.B.Ochilov; A.B.To’xtamishov (Universitas Muhammadiyah Sidoarjo, 2022)
This article discusses the importance of remote sensing data in the study of land resources, through which the current production process is carried out directly